Real-time tracking of energy flow in cluster formation - Michael Stadlhofer; Bernhard Thaler; Pascal Heim; Josef Tiggesbäumker; Markus Koch (Communications Chemistry)
Abstract Femtosecond time-resolved spectroscopy has shaped our understanding of light-matter interaction at the atomic level. However, the photoinduced formation of chemical bonds, especially for larger aggregates, has evaded observation due to difficulties to prepare reactants at well-defined initial conditions. Here, we overcome this hurdle by taking advantage of the exceptional solvation properties of superfluid helium, which allow us to stabilize atoms in a metastable, foam-like configuration with 10 Å interatomic distance. We apply photoexcitation with a femtosecond laser pulse to collapse such a dilute metastable aggregate of Mg atoms formed inside a nanometer-sized He droplet, and track cluster formation at a characteristic time of (450 ± 180) fs through photoionization with a time-delayed second pulse. We find that energy pooling collisions of electronically excited Mg atoms occur during cluster formation, leading to transient population of highly-excited Mg atoms, up to 3 eV above the excitation photon energy. Relaxation and conversion to nuclear kinetic energy drives cluster fragmentation and ejection of ionic fragments from the droplet. Our results demonstrate the potential of He droplets for bond formation studies, and for revealing involved energy- and charge transfer dynamics, like photon energy upconversion.